Roh Jahat Yang Dari Pada Tuhan? Tafsir Historis-Kultural 1 Samuel 16:14-23 Dengan Kaitannya Terhadap Kesehatan Mental - Olimbovo, Senopati Salomo (Sekolah Tinggi Teologi Baptis Indonesia, 2024)
Many Christians have, since childhood, acquired a dogmatic understanding that God cannot do anything that is not good nor evil. However, what should we do when confronted with 1 Samuel 16:14-23, which explicitly states that